The Impact of Innovation on The Competitiveness of Building Construction Projects - Dar Amer, Sabreen Fayiz (2019)
A Master of Science thesis in Civil Engineering by Sabreen Fayiz Dar Amer entitled, “The Impact of Innovation on The Competitiveness of Building Construction Projects”, submitted in July 2019. Thesis advisor is Dr. Salwa Beheiry and thesis co-advisor is Dr. Jamal El-Din Abdalla. Soft and hard copy available.